Heartwood : [large type] a novel - Gaige, Amity, 1972- (Center Point Large Print, 2025)
"In the heart of the Maine woods, an experienced Appalachian Trail hiker goes missing. She is forty-two-year-old Valerie Gillis, who has vanished 200 miles from her final destination. Alone in the wilderness, Valerie pours her thoughts into fractured, poetic letters to her mother as she battles the elements and struggles to keep hoping. At the heart of the investigation is Beverly, the determined Maine State Game Warden tasked with finding Valerie, who leads the search on the ground. Meanwhile, Lena, a seventy-six-year-old birdwatcher in a Connecticut retirement community, becomes an unexpected armchair detective. Roving between these compelling narratives, a puzzle emerges, intensifying the frantic search, as Valerie's disappearance may not be accidental. The mystery inspires larger questions about the many ways in which we get lost, and how we are found."--